The Creation of new autnonomous regions: Is this a solution for regional welfare ? - Nahdatun Nisa Mubai; Dede Sri Kartini; Novie Indrawati Sagita (Universitas Pancasakti Tegal, 2024)
This research analyzes whether expansion is a solution based on a competitive perspective, with a focus on the Nagari expansion in West Pasaman Regency. We collected data for this research using a qualitative approach through in-depth interviews with key informants from the Nagari government and local communities. The findings indicate that a nagari's expansion does not necessarily lead to its advancement. Many new nagari have not been optimal in managing resources, and there are ownership conflicts and competition between the parent region and newly emerging nagari, as well as the political transition process, which is hampering sustainable development. Therefore, while regional expansion offers new opportunities, the obstacles encountered underscore the necessity of assessing and enhancing policies to ensure the community's sustainable benefits and the attainment of Nagari autonomy.